Supramaximal-Exercise Training Improves Heart Rate Variability in Association With Reduced Catecholamine in Obese Adults - Jabbour, Georges; Iancu, Horia D. (Frontiers in Physiology, 2021)
This study investigates the effect of 6 weeks of supramaximal exercise training (SET) on heart rate variability (HRV) and associated factors in sedentary obese (OB) and normal-weight (NW) adults. In this study, 19 OB (22.9 (8.4) years; body mass index (BMI) (33.4 (1.4) kg/m2 and 18 NW (23.2 (4.4) years; BMI (18.7 (1.2) kg/m2) adults completed a 6-week SET intervention. Anthropometric and aerobic indicators as well the homoeostasis model assessment index for insulin resistance index (HOMA-IR) were assessed at baseline and after SET. The low- and high-frequency [(LF (0.03–0.15 Hz) in ms2 and HF (0.15-0.4 Hz) in ms2)] analysis of HRV as well as adrenaline (A in nmol/l) and noradrenaline (NA in nmol/l) responses were assessed at resting condition and during ventilatory threshold 1 (VT1) of a graded maximal test at baseline and after SET. At baseline, resting HF, LF and the LF/HF ratio were different among groups (P< 0.01, respectively) and were significantly associated with waist-to-hip ratio (β=-0.26; p=0.01, β=-0.12; p=0.01 and, β=0.21; p=0.01). During exertion at VT1, only LF/HF ratio was associated with NA responses (β=0.23; p=0.01). After SET, the frequency domain marker improved significantly for both groups in comparison to baseline. These improvements are manifested by LF and HF increases and LF/HF ratio decreases in the rest condition (p<0.01, respectively) and during exertion at VT1 (p<0.01, respectively). The improvement in LH and HF were associated with VO2max increases (β=0.22 p=0.01 and β=0.33; p=0.01). The decreases observed for the LF/HF ratio are mainly associated to NA decreases observed at rest (β=0.31; p=0.001) and at VT1 (β=0.38; p=0.001). Obese adults have altered HRV, and 6 weeks of SET improves HRV variables at rest and during VT1 exertion. While LF and HF improvement were associated with VO2max increases, the LF/HF ratio was mainly associated with noradrenaline decreases observed at rest and at VT1.